Effect of non-thermal atmospheric pressure plasma on wound bacteria and cell proliferation / Norhayati Mohd Nasir - Norhayati , Mohd Nasir (2020)
Non-thermal plasma produced in the plasma jet at atmospheric pressure consists of many reactive species and free radicals. The use of the atmospheric plasma jet has been expanded from surface treatment on polymers and biomaterials to the application as plasma medicine. It has been studied as a tools for wound sterilizations, enhance wound healing, topical treatment of skin diseases caused by bacteria infection and cancer therapy in recent research. The current study aims to investigate the effect of plasma on chronic wound bacteria as a supplementary to wound management particularly for compromised patients. The common practice in wound management is systemic antibiotic therapy that of poor penetration to specific region of tissues like wounds caused by burns. In the application of the non-thermal plasma in wound therapy, the antiseptic effect on bacteria inhibition is confirmed and its effect on the growth of the fibroblast cells is revealed. Two dielectric barrier discharge (DBD) configurations, planar DBD and capillary configuration powered by (AC) and direct current (DC) sources were employed to generate non-thermal plasma. The electrical characteristics was measured and emission spectroscopy was obtained. The analysis based of the current-voltage and power measurements gave the properties of the non-thermal plasma. The methicillin resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa (PA) isolated from chronic wound bacteria strains were treated with the non-thermal plasma for a duration of 10 mins to 60 mins. The efficacy of the plasma jet was further investigated on bacteria lawn. E coli lawn with short exposure from 10 s to 120 s. Fibroblast cells were also treated with plasma jet with AC powered to test the potential toxicity of plasma. The fibroblast cells were subjected to the non-thermal plasma at distant of 5 mm, 10 mm, 15 mm and 20 mm. The plasma dosage has been calculated by using multiple linear regression. It is found that low dosage of plasma produces cell proliferation effect. This results suggests that non-thermal plasma has advantage in wound management not only by its antiseptic effects but also simulate cell proliferation thus promote healing at specified treatment conditions.